Analysis of the Accounting Information System for Purchases of Merchandise in an Effort to Improve Internal Control at PT. Riau Abdi Sentosa - Bongmini, Elisabet (Nexus Synergy: A Business Perspective, 2023)
This research aims to find out what the accounting system for purchasing merchandise at PT. Riau Abdi Sentosa Pekanbaru, to find out whether the system is effective, and to find out what the internal control system is for purchasing merchandise at PT. Riau Abdi Sentosa. This research uses qualitative data. Implementation of an accounting analysis system at PT. Riau Abdi Sentosa has been run very well. There is a separation of purchasing functions, goods receiving functions, accounting functions, and warehouse functions. All documents are authorized by the responsible department. Healthy practices have been carried out in accordance with applicable internal controls. Researchers can provide suggestions so that companies can improve work discipline in order to achieve company goals optimally.